Comparison of transvenous vs subcutaneous defibrillator therapy in patients with cardiac arrhythmia syndromes and genetic cardiomyopathies. (15th January 2021) - Kuschyk, Jürgen; Müller-Leisse, Johanna; Duncker, David; Tülümen, Erol; Fastenrath, Fabian; Fastner, Christian; Kruska, Mathieu; Akin, Ibrahim; Liebe, Volker; Borggrefe, Martin; Veltmann, Christian; Rudic, Boris
Abstract: Background: Inherited arrhythmia syndromes and genetic cardiomyopathies attribute in a significant proportion to sudden cardiac death. Implantable cardioverter defibrillators (ICDs) are the cornerstone in the prevention of sudden death in high-risk patients. However, ICD therapy is also associated with high rates of inappropriate shocks and/or device-related complications especially in young patients. Objective: To determine the outcome of high-risk patients with inherited arrhythmia syndromes and genetic cardiomyopathies comparing two defibrillator technologies. Method: Between 2010 and 2018, 183 consecutive patients from two large German tertiary care centers were enrolled in the study. The majority of patients (83%) had either cardiac channelopathies or idiopathic ventricular fibrillation without cardiac structural abnormalities, while the remaining 17% had a genetic cardiomyopathy (HCM/ARVC). Eighty-six patients (47%) received a transvenous ICD (TV-ICD), while a subcutaneous ICD (S-ICD) was implanted in another 97 patients (53%). Results: During a mean follow-up of 4.3 years, 30 patients had an appropriate ICD therapy (annual rate 3.8%). Fifteen patients experienced an inappropriate shock (annual rate 1.9%). Lead failure occurred in 17 (9%) patients and was less frequent in the S-ICD group (OR 0.48, 95%CI 0.38–0.62). Adverse defibrillator events, defined as a composite of inappropriate shocks and lead failure requiring surgical revision were significantly lower in the S-ICD group as compared to the TV-ICD group (OR 0.55, 95%CI 0.41–0.72). There was a non-significant trend towards lower appropriate shocks in the S-ICD group, that in combination with all-cause shocks yielded in a significantly higher freedom of any shock in the S-ICD group (RR 39%, p  = 0.003). No deaths occurred during follow-up. Conclusion: The present data favor the use of the subcutaneous ICD for patients with inherited arrhythmia syndromes and genetic cardiomyopathies who do not need anti-bradycardia pacing. Highlights: High rates of appropriate shocks were observed in patients with inherited arrythmia syndromes and genetic cardiomyopathies. Appropriate therapies were mainly offset by inappropriate therapies and lead failures in transvenous ICDs. Subcutaneous ICD may help lowering the rate of appropriate and inappropriate shocks and thereby improve patient outcomes.